A social semiotic approach to ludonarrative assonance in the discourse of Metal Gear Solid V Series and Ghost of Tsushima - Kurniawan, Muhammad Hafiz; Sudana, Dadang; Gunawan, Wawan; Maftukhin, Maftukhin; Hadiyani, Teni; Puspasari, Wikandari Marselina (Universitas Islam Sultan Agung, 2025)
Video game has been in high demand recently and the historical events as the settings of video games in Metal Gear Solid V series and Ghost of Tsushima make the story of the video games more immersive. However, how this video games story and their gameplay system interact are not addressed yet from social semiotic perspective. From this perspective, this study aims to analyze the story of two mentioned video games and how this story can be in balance with its gameplay system. This research also offers an alternative point of view of how narratology and ludology should collaborate in video game discourse. This research used social semiotic approach, applying Kress and van Leeuwen Analysis on moving images and genre analysis by Martin and Rose. The data of this research are video game narratives and gameplay system This study used four steps: collecting, viewing and logging, taking sample, and analyzing the data in collecting and analyzing technique as an adaptation of the multimodal method from Bezemer and Jewitt. The result of this study shows that those selected video games were developed into what Ensslin stated about Mastery-Mentoring-Choice category for the protagonist. The meso-macro level of discourse in two mentioned video games allow the players to upgrade weapons and equipment without disturbing the flows of the story. In Metal Gear Solid V series, the stories flows with orientation-complication-temporary resolution pattern, and the gameplay allow players to upgrade the base because of having main mission to help other nations from colonialism. Meanwhile, in Ghost of Tsushima, the story flows with orientation-complication-resolution pattern and the gameplay allows players only to upgrade character skills because of having main mission to fight the invaders. Future scholars can address the micro-meso analysis in social semiotics and how the video game players make their choices.